2009
DOI: 10.1007/s12012-009-9052-4
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Preservation in Celsior Versus Histidine Buffer Solution During Cardiac Ischemia and Reperfusion

Abstract: Various stressful conditions such as ischemia in cold cardioplegic solutions and reperfusion occur during heart transplantation. Since ATP production is essential for the maintenance of contractile activity, mitochondrial function may be a mediator of ischemia and ischemia/reperfusion (I/R) injury. We aimed at testing the ability of two distinct cardioplegic solutions, Celsior (Cs) and Histidine Buffer (HBS), to protect rat heart mitochondria (HM) function during ischemia alone or ischemia followed by reperfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In our previous studies, we have concluded that hearts from females are less sensitive to oxidative stress in I/R conditions (16). Clinically, women are known to have less mortality resulting from coronary heart disease than men (33); accordingly, estrogen treatment increases superoxide dismutase (34) and decreases oxidative damage (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, we have concluded that hearts from females are less sensitive to oxidative stress in I/R conditions (16). Clinically, women are known to have less mortality resulting from coronary heart disease than men (33); accordingly, estrogen treatment increases superoxide dismutase (34) and decreases oxidative damage (35).…”
Section: Discussionmentioning
confidence: 99%
“…The ischemia protocol was performed according to previously described procedures (15,16). Briefly, after intraperitoneal anesthesia using ketamine (50 mg/kg) plus largactil (10 mg/kg), animals were sacrificed and an incision was made in the abdominal area.…”
Section: Study Groupsmentioning
confidence: 99%
“…In the reperfused myocardium, excess calcium invades the mitochondria [35] and triggers noticeable ROS production [36]. ROS inhibit the aconitase enzyme within the Krebs cycle [37], which blocks ATP synthesis and triggers the functional abnormalities that characterize reperfusion [38]. Obesity may modulate mitochondrial ROS production and the recovery of cardiac functional activity during reperfusion.…”
Section: Introductionmentioning
confidence: 99%
“…We have described in previous studies [Alves et al, 2009, 2011a] the mitochondrial protection afforded by both Celsior (Cs) and Histidine buffer (HBS), as well as how both solutions regulate substrate preference during I/R. In both studies, it was concluded that HBS proved to be a good alternative to Cs.…”
mentioning
confidence: 99%
“…The aim of the present work was to compare the protection afforded by two cardioplegic solutions: the worldwide clinically used Cs, and an emerging solution in clinical and experimental research, HBS [Takeuchi et al, 1999a,b; Alves et al, 2009], against several apoptotic signaling events in hearts subjected to ischemia alone and I/R. Two distinct preservation periods were investigated to compare the effect of moderate (4 h) versus severe ischemia (6 h).…”
mentioning
confidence: 99%